Evaluation of left atrial function and the relationship between left atrial stiffness index and exercise capacity in hypertension-related heart failure with preserved ejection fraction - Zhang, Qingfeng; Wang, Sijia; Zhang, Hongmei; Wang, Kai; Li, Wenhua; Ding, Geqi; Ye, Luwei; Li, Chunmei; Deng, Yan; Wang, Yi; Yin, Lixue (Frontiers in Cardiovascular Medicine, 2024)
ObjectiveThe left atrial stiffness index (LASI) holds significance in the atrioventricular coupling function and heart failure progression. To assess left atrial function and evaluate the relationship between LASI and exercise capacity in hypertension-related heart failure with preserved ejection fraction (HT-HFpEF).MethodsThe study involved 62 healthy subjects and 163 patients with HT (112 patients in simple HT group and 51 patients in HT-HFpEF group). Each patient performed exercise stress test and standard ultrasonic images were evaluated. A comprehensive evaluation of atrioventricular function, along with investigation into the correlation between these functional parameters and exercise capacity. And further to investigate the feasibility of predicting exercise intolerance using three-dimensional derived left atrial strain index (LASI) (E/e'/LASr and E/e'/LASr-c).ResultsCompared to healthy subjects, HT group demonstrated the elevation in left atrial volume accompanied by decrease in strain value (P < 0.05). In HT-HFpEF group, further significant reductions were observed in both longitudinal (LASr) and circumferential strain (LASr-c, LASct-c) (P < 0.05). Univariate regression demonstrated that both E/e'/LASr and E/e'/LASr-c were significantly correlated with metabolic equivalents (METs) (r = −0.462, P < 0.001; r = −0.381, P < 0.001). The E/e'/LASr demonstrates comparable diagnostic efficacy to exercise-E/e' in assessing exercise intolerance in HT-HFpEF patients (AUC: 0.836 vs. 0.867, P = 0.239).ConclusionProgressive LA remodeling contributes to decreased atrioventricular compliance in HT and HT-HFpEF patients.E/e'/LASr serves as an independent indicator of exercise intolerance in patients with HT-HFpEF.